1995
DOI: 10.1002/1097-0142(19950915)76:6<941::aid-cncr2820760606>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin and urokinase-type plasminogen activator tissue status in gastric carcinoma

Abstract: Background. E‐cadherin (ECD) is known to be an invasion suppressor gene, and urokinase‐type plasminogen activator (uPA) plays a central role in infiltration of solid cancers. Methods. To elucidate the relationship between expression of these factors and metastasis in patients with gastric cancer, the authors examined immunohistochemically a combination analysis of uPA and E‐cadherin expression in 98 primary tumors, and the results were correlated with several parameters related to metastasis. Results. Among 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 23 publications
2
30
1
Order By: Relevance
“…detected gastric cancer exist, prognosis of advanced gastric cancer still remains poor (40). Prognosis of gastric carcinoma patients depends on several pathological and genetic variables, such as TNM grading and p53, MUC1, and E-cadherin (41)(42)(43)(44). However, patient outcome is difficult to predict using classic histological and molecular classifications.…”
Section: Discussionmentioning
confidence: 99%
“…detected gastric cancer exist, prognosis of advanced gastric cancer still remains poor (40). Prognosis of gastric carcinoma patients depends on several pathological and genetic variables, such as TNM grading and p53, MUC1, and E-cadherin (41)(42)(43)(44). However, patient outcome is difficult to predict using classic histological and molecular classifications.…”
Section: Discussionmentioning
confidence: 99%
“…These activated forms digest the extracellular matrix of SGC tissues. 44,45 In addition, HGF stimulates the production of plasminogen activator and promatrix metalloproteinase. 46,47 The effects of NK4 on these candidates for gefitinib-resistance may be elucidated by further studies.…”
Section: Figurementioning
confidence: 99%
“…Several studies have reported that decreased function of E-cadherin is associated with tumour progression in many cancers, and in particular E-cadherin acts as a suppressor of invasive ability (Behrens et al, 1989;Vleminckx et al, 1991;Hirohashi, 2000). Many immunohistochemical studies evaluating E-cadherin expression in tumour tissues have demonstrated that reduced expression of E-cadherin is frequently observed in cancer progression (Katagiri et al, 1995;Lipponen and Eskelinen, 1995;Yonemura et al, 1995;Tamura et al, 1996;Nakanishi et al, 1997;Umbas et al, 1997;Bankfalvi et al, 1999;Ghadimi et al, 1999;Gofuku et al, 1999;Zheng et al, 1999;Kase et al, 2000).…”
mentioning
confidence: 99%